2004
DOI: 10.1104/pp.104.046151
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Tobacco 42-kD Protein Kinase Activated by Osmotic Stress

Abstract: In tobacco (Nicotiana tabacum), hyperosmotic stress induces rapid activation of a 42-kD protein kinase, referred to as Nicotiana tabacum osmotic stress-activated protein kinase (NtOSAK). cDNA encoding the kinase was cloned and, based on the predicted amino acid sequence, the enzyme was assigned to the SNF1-related protein kinase type 2 (SnRK2) family. The identity of the enzyme was confirmed by immunoprecipitation of the active kinase from tobacco cells subjected to osmotic stress using antibodies raised again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 59 publications
5
68
1
3
Order By: Relevance
“…Several members of the SnRK3 subfamily have been extensively characterized. One of best studied kinases in the SnRK3 family is SOS2, which is required for sodium and K ϩ homeostasis and abiotic stress tolerance (15). The activity of SnRK3 kinases are regulated in a Ca 2ϩ -dependent manner, and their activity is induced by interactions with a calcineurin-B like Ca 2ϩ binding protein in response to abiotic stress (16)(17)(18).…”
mentioning
confidence: 99%
“…Several members of the SnRK3 subfamily have been extensively characterized. One of best studied kinases in the SnRK3 family is SOS2, which is required for sodium and K ϩ homeostasis and abiotic stress tolerance (15). The activity of SnRK3 kinases are regulated in a Ca 2ϩ -dependent manner, and their activity is induced by interactions with a calcineurin-B like Ca 2ϩ binding protein in response to abiotic stress (16)(17)(18).…”
mentioning
confidence: 99%
“…Published papers report that MAPK cascades play an important role in regulating NO signal (She and Song 2008;Asai et al 2008). Others report that protein kinase may play a role downstream of NO signal in plants under normal conditions or environmental stress (Kelner et al 2004;Lamotte et al 2004;Sokolovski et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…At least four members of this family were found activated in vivo during hyperosmotic stress, while in a transient expression system nine of them were activated by hyperosmotic stress using mannitol and NaCl (Boudsocq et al, 2004). Based on the amino acid sequence, a 42-kDa protein kinase (NtOSAK) activated by osmotic stress in tobacco (Nicotiana tabacum) has been assigned to the SnRK2 family (Kelner et al, 2004). A maize SnRK2b homologue (ZmSPK1) was shown to be expressed in roots, mature leaves and vassels but most abundantly in the reproductive organs (Zou et al, 2006).…”
Section: Snf1 Related Kinase 2 (Snrk2s)mentioning
confidence: 99%
“…In vitro treatment with phosphatases has shown that kinase phosphorylation is important for activation: Tobacco homolog of Arabidopsis SnRK2 (ASK1/ SnRK2.4) purified from BY-2 cells was inactivated by protein phosphatase 2A (PP2A) (Miklajczyk et al, 2000;Kelner et al, 2004); alkaline phosphatase abolished salt activation of two rice SnRK2s, SAPK1 and SAPK2 (Kobayashi et al, 2004). Suppression of OST1 kinase activation in response to ABA in the dominant abi1-1 mutant (Mustilli et al, 2002) provided the evidence for negative regulation of ABA signal transduction upstream of OST1 by protein phosphatase 2C (PP2C) ABI1 (Koornneef et al, 1984;Leung et al, 1994).…”
Section: Regulation and Activity Of Snrk2mentioning
confidence: 99%
See 1 more Smart Citation